Rationality and Reasonableness in the Causal Chain: a new model to support legal decision-making - Crane, Kathryn J (2009)
This dissertation considers the concepts of rationality and reasonableness within the fields of economics and law respectively. An examination of the relevant literature within these fields is conducted, together with a consideration of concepts in the literature of other fields including psychology, philosophy and the press. Extensive critiques of both concepts are presented here and yet it is maintained that they are nonetheless of significant importance.